Adipose Tissue-Derived Stem Cells Differentiate into Carcinoma-Associated Fibroblast-Like Cells under the Influence of Tumor-Derived Factors - Constantin Jotzu; Eckhard Alt; Gabriel Welte; Jie Li; Bryan T. Hennessy; Eswaran Devarajan; Srinivasalu Krishnappa; Severin Pinilla; Lilly Droll; Yao-Hua Song (Analytical Cellular Pathology)
Carcinoma-associated fibroblasts (CAF) are considered to contribute to tumor growth, invasion and metastasis. However, the cell type of origin remains unknown. Since human adipose tissue-derived stem cells (hASCs) are locally adjacent to breast cancer cells and might directly interact with tumor cells, we investigated whether CAFs may originate from hASCs. We demonstrated that a significant percentage of hASCs differentiated into a CAF-like myofibroblastic phenotype (e.g., expression of alpha smooth muscle actin and tenascin-C) when exposed to conditioned medium from the human breast cancer lines MDAMB231 and MCF7. The conditioned medium from MDAMB231 and MCF7 contains significant amounts of transforming growth factor-beta 1 (TGFβ1) and the differentiation of hASCs towards CAFs is dependent on TGFβ1 signaling via Smad3 in hASCs. The induction of CAFs can be abolished using a neutralizing antibody to TGFβ1 as well as by pretreatment of the hASCs with SB431542, a TGFβ1 receptor kinase inhibitor. Additionally, we found that these hASC-derived CAF-like cells exhibit functional properties of CAFs, including the ability to promote tumor cell invasion in an in vitro invasion assay, as well as increased expression of stromal-cell-derived factor 1 (SDF-1) and CCL5. Taken together, these data suggest that hASCs are a source of CAFs which play an important role in the tumor invasion.